2015
DOI: 10.1186/s40623-015-0223-1
|View full text |Cite
|
Sign up to set email alerts
|

Vertical movements of the Murono mud volcano in Japan caused by the Naganoken Kamishiro Fault Earthquake in 2014

Abstract: We observed vertical movements of the Murono mud volcano, Niigata, Japan, caused by the Naganoken Kamishiro Fault Earthquake (M = 6.7) on 22 November 2014. Precise levelling around the mud volcano was carried out on 27 November 2014, and the obtained elevation was compared with the data obtained for 11 November 2014. It was found that an elliptical uplift area, about 46 mm in magnitude and an order of magnitude smaller than that of the ones formed due to the past movements caused by the earthquakes in the same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…This suggests that the 2014 earthquake likely affected the spatial pattern, including both uplift and subsidence. The maximum uplift (30 mm) in this period roughly corresponds to that derived from a leveling survey (46 mm, Kusumoto et al 2015) but is less than that observed in period I. This may be attributed to the relatively low acceleration experienced in the area (0.22 cm/s 2 ) in the 2014 earthquake (Table 2).…”
Section: Temporal Changes In Surface Elevationsupporting
confidence: 47%
See 4 more Smart Citations
“…This suggests that the 2014 earthquake likely affected the spatial pattern, including both uplift and subsidence. The maximum uplift (30 mm) in this period roughly corresponds to that derived from a leveling survey (46 mm, Kusumoto et al 2015) but is less than that observed in period I. This may be attributed to the relatively low acceleration experienced in the area (0.22 cm/s 2 ) in the 2014 earthquake (Table 2).…”
Section: Temporal Changes In Surface Elevationsupporting
confidence: 47%
“…1c). The western side of the site is partially deformed, while the center of the site, which contains a vent, does not show obvious uplift (Kusumoto et al 2014(Kusumoto et al , 2015. In contrast, the eastern side has particularly large and frequent deformations.…”
Section: Study Sitementioning
confidence: 95%
See 3 more Smart Citations